Fatal breakthrough mucormycosis in a multivisceral transplant patient receiving micafungin: Case report and literature review. (2018) - Louis-Auguste, John R.; Micallef, Christianne; Ambrose, Tim; Upponi, Sara; Butler, Andrew J.; Massey, Dunecan; Middleton, Stephen J.; Russell, Neil; Rutter, Charlotte S.; Sharkey, Lisa M.; Woodward, Jeremy; Gkrania-Klotsas, Effrossyni; et al.
Abstract: Introduction: Antifungal agents are routinely used in the post-transplant setting for both prophylaxis and treatment of presumed and proven fungal infections. Micafungin is an echinocandin-class antifungal with broad antifungal cover and favorable side effect profile but, notably, it has no activity against molds of the order Mucorales. Presentation of case: A 47-year-old woman underwent multivisceral transplantation for intestinal failure-associated liver disease. She had a prolonged post-operative recovery complicated by invasive candidiasis and developed an intolerance to liposomal amphotericin B. In view of her immunosuppression, she was commenced on micafungin as prophylaxis to prevent invasive fungal infection. However, she developed acute graft versus host disease with bone marrow failure complicated by disseminated mucormycosis which was only diagnosed post mortem. Discussion: Non- Aspergillus breakthrough mold infections with micafungin therapy are rare with only eight other cases having been described in the literature. Breakthrough infections have occurred within one week of starting micafungin. Diagnosis is problematic and requires a high degree of clinical suspicion and microscopic/histological examination of an involved site. The management of these aggressive infections involves extensive debridement and appropriate antifungal cover. Conclusion: A high level of suspicion of invasive fungal infection is required at all times in immunosuppressed patients, even those receiving antifungal prophylaxis. Early biopsy is required. Even with early recognition and aggressive treatment of these infections, prognosis is poor.